APPLICATION OF " SPOC + FLIPPED CLASSROOM " IN CHINESE CLASSROOM OF FOREIGN COLLEGE STUDENTS - CeMei, Li; Rahman , Mohd Nazri Abdul; Affandi , Ghozali Rusyid; Wang, Jianping (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: With the rapid advancement of information technology, digital learning has become a key direction in the reform of higher education. Among various innovative models, the combination of Small Private Online Course (SPOC) and flipped classroom has attracted increasing attention due to its blended format and emphasis on learner engagement and feedback. This study investigates the application of the “SPOC + flipped classroom” model in Chinese language classrooms for international students in China. Through literature analysis, questionnaires, and interviews, the study explores the current situation, problems, and underlying causes of international students learning effectiveness, learning attitudes, and learning satisfaction. Data were collected from five universities in Yunnan Province and analyzed using tools such as SPSS, Mplus, and NVivo. Additionally, an experimental design was employed to compare the teaching outcomes between an experimental group and a control group. The findings aim to provide new insights and practical approaches for enhancing Chinese language teaching for international students and promoting the localized implementation of blended learning.